Genetic Variation of Corona Virus: A Review - Hammadi, Amer A.; Al-Mousawi, Masar R. R. (Scientific Journal of Medical Research, 2021)
Objective: COVID-19 is a unique coronavirus that caused a pandemic after an epidemic of atypical viral pneumonia in Wuhan, China. COVID-19 is classified by genomic architecture and phylogenetic relationships as Beta coronavirus. Beta coronaviruses human-like SARS-CoV, SARS-CoV-2, and MERS-CoV) share several characteristics; however, their phenotypic and genomic structures differ, which affects pathogenesis. Within a matrix protein-based capsid, single-stranded (positive-sense) RNA genetic makeup of COVID-19 coupling together with a nucleoprotein. In the genome of normal CoV, there are at least six ORFs. The segments of RNAs of CoVs were utilized to translate all structural and supplement proteins. On the one-third of the genome (ORFs 10, 11) around 3’-terminal encoding four main structural proteins. COVID-19 phenotypic and genetic have a role of an organization through pathogenesis is stringent. In comparison to other Beta coronaviruses, this article focuses on the most important of these characteristics. Conclusion: This study gives an overview of the current COVID-19 scenario and depicts the case of the technique in terms of public health effects in clinical manifestations, diagnosis, pathophysiology, emergency response, preparedness, and case management. There are a lot of literature fasts developing on this subject, which shill assist in the evolution of a felicitous vaccine and better management with treatment practices for a casual situation. Just once the pestilence is high will have the ability to analyze the health, gregarious, economic outcome of this pandemic calamity. We should draw lessons for future pandemics, particularly in terms of public and global health.